GAMBARAN KARAKTERISTIK PASIEN HIPERTENSI DI RUMAH SAKIT UMUM FULL BETHESDA MEDAN TAHUN 2021 - Rusmauli Lumban Gaol; Friska Novalina Simbolon (Jurnal Online Keperawatan Indonesia, 2022)
Hypertension is a non- communicable disease that is one of the main causes of premature death in the world. The World health Organization (WHO) estimates that in 2025 there will be an increase in hypertension cases by around 80%, in 2000 from 639 million cases to 1.5 billion cases. Hypertension is the third leading cause of death in Indonesia for all ages. In 2015, surveys showed that 1 in 4 women and 1 in 5 men suffer from hypertension. Less than 1 in 5 people have hypertension that is well controlled and more than 9 million deaths are related to hypertension. The aim of this research is to describe the characteristic of hypertensive patient at the Full Bethesda General Hospital Medan in 2021. The method used is descriptive, with a total sampling technique of 105 people. The result of these research are respondents with hypertension at Full Bethesda General Hospital Mdan in 2021 range from 55-64 years (40.0%), female (54.28%), senior high school (56.19%),nor working (36.20%), Tribe of Toba Batak (48.58%). It can be concluded that the characteristic of hypertension can occur at the age between 55-64 years, female gender, senior high school,on average in the group who do not have job and toba batak tribe. The result of this research is expected to provide useful and to give knowledge for the hypertensive patient.